ONLINE LEAVE APPLICATION INFORMATION SYSTEM AT PT PERKEBUNAN NUSANTARA - Ahmad Ihsan; Resha Elfriyani; Melaty Aini Siregar (E-Jurnal Universitas Samudra, 2020)
Employees certainly get their rights in the workplace, one of them is right in getting leave. With the sophistication of technology owned by the company, it provides an opportunity for authors to create an online leave information system to make it easier for employees to apply for leave quickly. The system is built using the waterfall software development method or often be called as classic life cycle and with PHP as its programming language. The result of system is that this system can make employees more practical in the process of applying for leave while the employees are not in the company. This information system also allows admin to be quicker in submitting the leave request form to the leader to be followed up and then printed by the admin if it has been granted permission by the leader.